Characterization of smallholder mixed crop–livestock systems in integration with spatial information: In case Ethiopia - Amejo, A.G.; Gebere, Y.M.; Kassa, H.; Tana, T. (Informa UK Limited, 2019)
The mixed crop–livestock systems are acknowledged as sustainable due to its complementarity and synergy, contribution to welfare, food security, income, and poverty alleviation. The lack of efforts in the long-term impact for increased and more efficient food production, however, threatens the livelihoods and food security of smallholder producers. This paper provides a description on smallholder crop–livestock systems in the dominant system unit of crop and livestock production discretely subdividing in different agroecological zones (AEZs) into land-use land-cover class for considering factors influencing socioeconomic and agricultural intensification. A linear mixed-effects model was carried out to fit the relationship between the land-cover measurement and the corresponding farm enterprise in land use. The repeated measurements of linear predictors that fit in full and reduced model analysis were conducted in the system framework. The landscape slope (%), elevation (m) and market distance (minute) analysis were used in spatial adjustment in the specific system. The overall area of land-use system of the peasant holdings was 599.86 ha. The area covered by annual crops was 56%, which was higher (p < 0.01) compared to the area covered by natural pasturelands (17%), perennial crops (15%), vegetable (1%) and the tree or grass cover (2%). Distinct six farming systems were characterized, each being significantly different from other. The difference within a similar AEZ could probably be a result of a minor level of farm systems manipulation. The major difference associated could essentially be with a difference in agroecology and spatial variability of the farm households.